Colourfastness properties of natural dye from tagetes erecta on silk fabric using different dyeing techniques / Nur Amirah Fadzlena Md Fadzli ... [et al.] - Md Fadzli, Nur Amirah Fadzlena; Ruznan, Wan Syazehan; Ahmad Suhaimi, Suraya; Ahmad, Mohd Rozi; Ab Kadir, Muhammad Ismail; Mohd Nor, Mohd Azlin; Ariffin, Suhaidi (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Of late, dyeing fabrics with natural dyes have become an attraction because of its eco-friendly and less threatening disposition towards humankind. In the textile colouration industry, natural dyes play an important role because of the need for replacement synthetic dyes which have a great deal of tension with the environmental issues. This study focuses on the colour shade, colour coordinates, and fastness properties of dyed silk fabric from tagetes erecta (Mexican Marigold flower) using the water boiling extraction method. The dyeing was carried out using lemon juice as a natural mordant through the simultaneous mordanting method, using two different dyeing methods: infrared (IR) dyeing and exhaustion dyeing. The shades produced for exhaustion dyed fabric is light-yellow compared to the IR dyed fabric, which is medium-light yellow. These shades were confirmed with the CIELAB colour coordinates, L*a*b* values. The colourfastness to washing, perspiration, rubbing, and light of the fabrics were conducted to investigate the performance of the dye and mordant on the dyed silk fabrics. The colourfastness properties of the dyed silk fabric using infrared (IR) dyeing technique have better performance than using exhaustion dyeing technique.